Impact of influencer endorsement, brand ambassador, brand image, and brand awareness on purchase decision (a case study of Erigo brand) - Russel Ryan; Suwinto Johan (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
In Indonesia, the fashion industry from year to year is growing rapidly around the world, including Indonesia. All fashion industries have improved significantly from 2012-2020. In 2020 when the Covid-19 pandemic hit, the Fashion Industry also got the effect but also during that time, the online sector or, in other words, E-commerce drastically increased, that's why fashion apparel incredibly improving. Erigo apparel, as one of the famous fashion brands in Indonesia, also felt the effect of the increasing interest in the apparel industry, and with the innovative combination altogether, the demands of the Indonesian people were really at their peak. The improvement of the fashion industry, which contributes roughly 18.01 percent or Rp. 116 trillion to Indonesia's creative economy has sparked a lot of interest in the country's creative economy. The presence of this occurrence inspired the researcher to conduct a study about this phenomenon to find out what is the best way to increase the sales of the Erigo apparel brand and the growing buy of the people who get pursued by the marketing strategy of this apparel using these variables on how it impacted the purchase decision. The researcher will be using four independent variables such as influencer endorsement, brand ambassador, brand image, and brand awareness; one dependent variable is Purchasing Decision. The researcher will utilize a quantitative research approach and use non-probability sampling, more specifically snowball sampling. The total respondents of this study are 245 respondents, answering 25 statements using the Likert Scale method. The researcher will also be using SPSS as a tool to analyze all the data of this study. From the result, it can be concluded that there is a positive and significant influence of brand image and brand awareness on Purchasing Decisions, while influencer endorsement and brand ambassadors have a positive but insignificant influence on purchasing decisions.